Scientific production of renewable energies worldwide: An overview - Manzano-Agugliaro, F.; Alcayde, A.; Montoya, F.G.; Zapata-Sierra, A.; Gil, C. (Renewable & sustainable energy reviews, 2013)
This paper reviews the scientific production of renewable energies, namely, solar, wind, biomass, hydropower and geothermal, from 1979 to 2009. The production of all the countries in the world is analysed, paying particular attention to renewable energies and research institutions. The production of scientific research for each type of energy is represented on world maps to show the degree of relationship between this research and the resources of these energies. It is observed that biomass is the most studied, both by number of publications, with 56% of the publications on renewable energy, and by geographical distribution. The next in importance by number of publications is solar energy (26%). The countries investigating solar energy, however, are not necessarily those with the greatest availability of this resource. Wind is the third positioned in publication (11%). Wind is being investigated by countries that most have implemented this type of energy production. Hydro and geothermal energies are also investigated by countries with great abundance of this resource. It is observed that research on renewable energy is highly concentrated in a few countries (12 or 14, depending on the energy type), accounting for between 70 and 80% of scientific production. The role of the USA as a leader in research in all renewable energies studies is emphasised. NASA is the leading institution for solar and wind energy, the Chinese Academy of Sciences leads in hydropower and biomass, and the U.S. Geological Survey leads in geothermal energy.